2011
DOI: 10.1111/j.1365-2109.2010.02744.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of probiotic bacteria on growth parameters and immune defence in Eurasian perch Perca fluviatilis L. larvae under intensive culture conditions

Abstract: Two experiments were conducted to examine whether a mixture of bacteria composed of Bacillus licheniformis, Bacillus subtilis and Bacillus pumilus has a beneficial impact on survival, growth, lysozyme activity and total immunoglobulins (Ig) in perch larvae. In experiment 1, control fish were compared with fish receiving bacteria (4.93 × 107 CFU L−1 day−1) through tank water or both through tank water and Artemia metanauplii enriched with two bacteria doses (2 × 1010 or 4 × 1010 CFU L−1). Treatments were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 41 publications
(73 reference statements)
1
11
0
Order By: Relevance
“…Similar findings have been observed in tilapia (Adeoye et al., ; Liu et al., ; Lukkana et al., ; Silva et al., ), gilthead sea bream ( Sparus aurata ) (Avella et al., ) and Eurasian perch ( perca fluviatilis L .) (Mandiki et al., ) fed Bacillus ‐based probiotics. Many studies (Adeoye et al., ; Avella et al., ; El‐Haroun et al., ; Liu et al., ; Lukkana et al., ; Mandiki et al., ; Silva et al., ; Taoka et al., ) demonstrated the ability of Bacillus to colonize the gut of fish and accordingly enhance the production of organic acids, activation of digestive enzymes and detoxification of the harmful constituents of feeds and collectively maintain a healthy gut with a subsequent improvement in nutrient digestibility and absorption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings have been observed in tilapia (Adeoye et al., ; Liu et al., ; Lukkana et al., ; Silva et al., ), gilthead sea bream ( Sparus aurata ) (Avella et al., ) and Eurasian perch ( perca fluviatilis L .) (Mandiki et al., ) fed Bacillus ‐based probiotics. Many studies (Adeoye et al., ; Avella et al., ; El‐Haroun et al., ; Liu et al., ; Lukkana et al., ; Mandiki et al., ; Silva et al., ; Taoka et al., ) demonstrated the ability of Bacillus to colonize the gut of fish and accordingly enhance the production of organic acids, activation of digestive enzymes and detoxification of the harmful constituents of feeds and collectively maintain a healthy gut with a subsequent improvement in nutrient digestibility and absorption.…”
Section: Discussionmentioning
confidence: 99%
“…(Mandiki et al., ) fed Bacillus ‐based probiotics. Many studies (Adeoye et al., ; Avella et al., ; El‐Haroun et al., ; Liu et al., ; Lukkana et al., ; Mandiki et al., ; Silva et al., ; Taoka et al., ) demonstrated the ability of Bacillus to colonize the gut of fish and accordingly enhance the production of organic acids, activation of digestive enzymes and detoxification of the harmful constituents of feeds and collectively maintain a healthy gut with a subsequent improvement in nutrient digestibility and absorption. Recently, it was demonstrated that Bacillus can displace pathogenic bacteria from the gut and accordingly enhance disease resistance and improve fish performance (Addo et al., ; Hostins et al., ; Srisapoome & Areechon, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the administration of bacteria through water did not give rise to any significant increase in growth, survival, and immunity. It is possible that probiotic uptake by fishes with this administration mode was not sufficient to stimulate their digestive mechanisms [100]. Likewise, the direct addition of Lactobacillus spp.…”
Section: Treatment Dosementioning
confidence: 99%
“…Benefits linked to the use of probiotics have already been proved in many studies, such as their action in the competitive exclusion of pathogenic bacteria (Vine et al 2004), as sources of nutrients and digestive enzymes (Lazado et al 2012;Mehrabi et al 2012;Sun et al 2012), in the immune system modulation (Panigrahi et al 2004;Mouriño et al 2012), and in the production of bacteriocins and organic acids (Balc azar et al 2007c;Mahdhi et al 2011;Mandiki et al 2011;Silva et al 2013).…”
mentioning
confidence: 99%